Effects of Sleep Quality on Quality of Life in Patients with Osteoporosis - Şule Şahin Onat; Sibel Ünsal Delialioğlu; Seda Biçer (Galenos Yayinevi, 2013)
Aim: The purpose of the study was to evaluate sleep quality in osteoporotic individuals, and to determine the associated factors with sleep quality and to investigate the relationship between quality of life and sleep quality Material and Methods: 154 patients with osteoporosis admitted to our outpatient clinic included in the study. A questionnaire that was including patients age, sex, marital status, education level, occupation, height, weight, alcohol use, smoking, physical activity level, milk consumption and previous fragility fracture was completed. DXA was used to determine bone mineral density of the lumbar spine and femoral neck. Thoracal and lumbar compression fractures were evaulated with thoracal and lumbar radiography.Visual analog scale was used to evaluate back pain. Pittsburgh sleep quality index was used to determine sleep quality and QUALEFFO was used to evaluate quality of life in the individuals. Results: A total of 154 individuals included in the study. 65 patients (42.2%) had a sleep disorder and 89 patients (57.8%) hadn't a sleep disorder. Mean age, female gender, not being married, not working actively, illiteracy rates were higher; the mean of weekly consumption of milk were lower in patients with sleep disorders than without sleep disorders. Vertebral compression fracture was more in patients with sleep disorders than without sleep disorders. Both lumbar and femoral T and Z values, VAS values were significantly higher in patients with sleep disorders than without sleep disorders (p<0.05). The value of all sub-parameters of quality of life scale QUALEFFO and total value were significantly higher in patients with sleep disorders than without sleep disorders (p<0.05). Conclusion: Sleep disorders in patients with osteoporosis are releated to factors such as age, sex, marital status, education level and diet. Sleep disorders cause a further decrease in the quality of life of patients with osteoporosis. (Turkish Journal of Osteoporosis 2013;19: 32-7)